Antibacterial plant combinations prevent postweaning diarrhea in organically raised piglets challenged with enterotoxigenic Escherichia coli F18 - Jerez-Bogota, Kevin; Jensen, Martin; Højberg, Ole; Cormican, Paul; Lawlor, Peadar G.; Gardiner, Gillian E.; Canibe, Nuria (Frontiers in Veterinary Science, 2023)
Antibiotics and zinc oxide restrictions encourage the search for alternatives to combat intestinal pathogens, including enterotoxigenic Escherichia coli (ETEC), a major cause of postweaning diarrhea (PWD) in pigs. PWD causes important economic losses for conventional and organic farming. This study investigated the effect of dietary supplementation with garlic and apple pomace or blackcurrant on infection indicators and the fecal microbiota of organic-raised piglets challenged with ETEC-F18. For 21 days, 32 piglets (7-weeks-old) were randomly assigned to one of four groups: non-challenge (NC); ETEC-challenged (PC); ETEC-challenged receiving garlic and apple pomace (3 + 3%; GA); ETEC-challenged receiving garlic and blackcurrant (3 + 3%; GB). ETEC-F18 was administered (8 mL; 109 CFU/ml) on days 1 and 2 postweaning. The 1st week, PC had lower average daily gain than those in the NC, GA, and GB groups (P < 0.05). NC pigs showed neither ETEC-F18 shedding nor signs of diarrhea. The PC group had higher diarrhea incidence and lower fecal dry matter than NC (≈5–10 days; 95% sEBCI). The GA and GB groups showed reduced ETEC-F18 and fedA gene shedding, higher fecal dry matter, and lower diarrhea incidence than the PC (≈5–9 days; 95% sEBCI). The NC, GA, and GB had normal hematology values during most of the study, whereas the PC had increased (P < 0.05) red blood cells, hemoglobin, and hematocrit on day 7. Haptoglobin and pig-MAP increased in all groups, peaking on day 7, but PC showed the greatest increase (P < 0.05). The fecal microbiota of PC pigs had reduced α-diversity (day 7; P < 0.05) and higher volatility (days 3–14; P < 0.05). Escherichia, Campylobacter, and Erysipelothrix were more abundant in the PC than in the NC, GB, and GA groups (log2FC > 2; P < 0.05), whereas Catenibacterium, Dialister, and Mitsoukella were more abundant in the NC, GB, and GA than in the PC group (log2FC > 2; P < 0.05). Prevotella and Lactobacillus were more abundant in the GB group (log2FC > 2, P < 0.05). In conclusion, dietary supplementation of GA and GB limited ETEC proliferation, reduced PWD, and beneficially impacted the fecal microbiota's diversity, composition, and stability.